Design of 10 MeV cyclotron accelerator - R Solhju (Iranian Journal of Physics Research, 2015)
Design and construction of 10MeV cyclotron has been started at Amirkabir University of Technology since 2012. So far, the conceptual and detail engineering design phases have been finalized. The main purpose of this baby cyclotron is to generate proton beam for the production of PET radioisotopes. The cyclotron consists of magnet, cavity, ion source, RF and LLRF system, vacuum system, cooling system, power amplifiers and power supplies system. In this paper, a brief of design principles for all the parts of cyclotron and their final simulation results is presented. It should be noted that these simulations have been performed and optimized by the most accurate softwares such as TOSCA, ANSYS, HFSS, SolidWorks and CST. Also, the manufacturing feasibility of all the parts is performed and their dimensions and parameters are synchronized with manufacturing standards